Collective particle dynamics of molten NaCl by inelastic x-ray scattering. (15th July 2021) - Demmel, F; Hosokawa, S; Pilgrim, W-C
Abstract: An inelastic x-ray scattering experiment has been performed on molten NaCl over wide wave vector and energy transfer ranges. Data of high statistical quality are analyzed using a memory function approach within a generalized Langevin equation. The approach with two relaxation times for the memory function provides a very good data description over the whole wave vector range beyond the hydrodynamic regime. A slow thermal and a fast structural relaxation process in the memory function completely define the density fluctuations in molten NaCl and evidences the thermal-viscoelastic model as the minimal description for collective particle dynamics in molten alkali halides. The obtained excitation frequencies demonstrate a large positive dispersion effect, which can be related to the viscoelastic reaction of the molten salt. A transition from the viscoelastic to a hydrodynamic response of the molten salt at small wave vectors is observed. In the hydrodynamic regime the resulting thermal diffusivity agrees well with values obtained through light scattering. The modeling indicates some deficiencies at small wave vectors and large energy transfers and the spectra of the current correlation function evidences additional intensity at high frequency. The frequency of these additional modes approach a non-zero value at zero wave vector and indicates a non-acoustic character of these excitations. The frequency center of this additional inelastic intensity coincides with optic-type modes in molten NaCl predicted by simulations.